Θησαυρός Σκουριές Χαλκιδικής/2012 - Ντονάς Αλέξης (Tekmeria, 2025)
This article presents a hoard of 12 bronze coins that was discovered during archaeological excavation at the site of "Skouries" in NE Chalcidice. The hoard contains one bronze of the Amphaxians, one of the quaestor Gaius Publilius, six of the quaestor Lucius Fulcinnius, three of the city of Pella and one of Amphipolis. The description of the coins is as follows: no. 1: Head of Herakles r. / Club ΑΜΦΑ-ΞΙΩΝ, all in laurel wreath; nos. 2-7: Head of Rome r. / ΜΑΚΕΔΟΝΩΝ – ΤΑΜΙΟΥ ΛΕΥΚΙΟΥ – ΦΟΛΚΙΝΝΙΟΥ, all in laurel wreath; no. 8: Head of Rome r. / ΓΑΙΟΥ ΤΑΜΙΟΥ – ΠΟΠΛΙΛΙΟΥ, all in laurel wreath; nos. 9-11: Head of Rome r. / ΠΕΛΛΗΣ in laurel wreath; no. 12: Head of Poseidon r. / ΑΜΦΙΠΟ-ΛΙΤΩΝ in laurel wreath. Three more bronze coins found during the archaeological excavation near the hoard show strong corrosion and cannot be identified. Although small, the hoard from Skouries is of particular importance for the study of the late Hellenistic Macedonian bronzes, since it confirms the sequence of minting as has been proposed in recent scholarship: the coins of the Districts were the first non royal bronzes to be minted in Macedonia under the royal regime, followed by the issues of the Roman quaestors Lucius Fulcinnius and Gaius Publilius minted after the Roman conquest of 168 BC. The bronzes of Amphipolis, Thessalonike and Pella, capitals of the three districts, were produced after those of the quaestors. The material in the hoard illustrates, in the most eloquent way, the continuity of coinage in a turbulent period for the region of Macedonia and, furthermore, it confirms the suggestion of Kourempanas that the civic bronzes with the head of Roma / ethnic and the head of Poseidon / AΜΦΙΠΟΛΙΤΩΝ were amongst the earliest civic issues. The concealment of the Skouries/2012 hoard took place certainly after 168 BC. Taking into account the evidence of the wear of the coins, it could have been concealed in c. 165 BC.